2021
DOI: 10.5937/selsem2101007k
|View full text |Cite
|
Sign up to set email alerts
|

Variability and interdependence of characteristics of maize hybrids of different vegetation lengths

Abstract: Maize is one of the most important field crops with broad genetic and phenotypic variations. It occupies an important place in agricultural production in the world as in Serbia. The main aim of maize breeding is to obtain new inbred lines, i.e. to identify new hybrid combinations that will surpass existing hybrids in terms of grain yield and other important traits. The aim of this study was to examine the phenotypic variability of 10 NS maize hybrids of different genetic bases and maturity groups in agroecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Yield is a complex trait; hence, the genotype that has a balanced ratio and high values of certain yield components will result in a higher yield. These results are in agreement with those obtained by [77]. However, the obtained results indicated that in maize genotypes, aside from the effects of different treatments, climatic conditions were affected by significant differences in certain yield traits.…”
Section: Kernel Number Per Rowsupporting
confidence: 92%
See 1 more Smart Citation
“…Yield is a complex trait; hence, the genotype that has a balanced ratio and high values of certain yield components will result in a higher yield. These results are in agreement with those obtained by [77]. However, the obtained results indicated that in maize genotypes, aside from the effects of different treatments, climatic conditions were affected by significant differences in certain yield traits.…”
Section: Kernel Number Per Rowsupporting
confidence: 92%
“…However, the obtained results indicated that in maize genotypes, aside from the effects of different treatments, climatic conditions were affected by significant differences in certain yield traits. Similar findings regarding the importance of climatic factors have also been reported by [77][78][79][80].…”
Section: Kernel Number Per Rowsupporting
confidence: 87%
“…Correlation reflects the linear dependence between two variables, but two variables can also be strongly dependent without linear connection. Therefore, a multivariate analysis such as PCA is considered very useful for a full understanding of the interrelationship between large numbers of variables (Krstić et al, 2021). Table 4.…”
Section: ____________________________________________________________...mentioning
confidence: 99%